Burst or conventional peripheral nerve field stimulation for treatment of neuropathic facial pain - Manning, A; Fitzgerald, J; Green, A; Aziz, T; Bojanic, S; Garcia, R; Moir, L; Edwards, T (Wiley, 2019)
Background Trigeminal Neuropathic Pain (TNP) is a chronic facial pain syndrome caused by a lesion or disease affecting one or more branches of the trigeminal nerve. It may, for example, result from accidental injury to a branch of the trigeminal nerve by trauma or during surgery; it may also be idiopathic. TNP is typically constant, in contrast to most cases of the commoner trigeminal neuralgia. In some cases, pain may be refractory to pharmacological treatment. Peripheral nerve field stimulation is recognized as an effective minimally invasive surgical treatment option for this debilitating condition. To date, stimulation has used conventional tonic waveforms, which generate paraesthesia in the stimulated area. This is the first report of the use of paraesthesia‐free burst pattern stimulation for TNP. Methods Seven patients were treated at the John Radcliffe Hospital for TNP from 2016 to 2018. Mean duration of preoperative symptoms was five years. All patients had exhausted pharmacological measures to limited effect. The initial three patients had tonic stimulation with the subsequent four having burst stimulation. Outcome was assessed using the numeric pain rating scale preoperatively and postoperatively at three and six months and one year. Side‐effects and complications were also assessed as well as reduction in analgesic medication use. Results All patients achieved pain reduction of at least 50% at 6 months (range 50–100%, mean 81%, p = 0.0082). Those in the burst stimulation group were paraesthesia free. One patient developed a postoperative infection for which the system had to be removed and is awaiting reimplantation. There were no other complications in either group. Conclusion Burst stimulation conferred similar pain control to tonic stimulation in our small cohort, and there were similar reductions in pain medication use. An additional benefit of burst stimulation is freedom from paraesthesia. Larger scale studies are needed to further evaluate burst stimulation and compare its efficacy with that of tonic stimulation.